Avaliação de variáveis de qualidade da água e contaminantes ambientais emergentes em águas de consumo humano no Rio Grande do Sul - Seben, Débora (2020)
The properties of water suffer from different types of interference, whether natural or anthropic, and it is essential to know these characteristics in order to later determine their purpose. The objective of this research was to qualify and quantify the physical, chemical, microbiological and emerging environmental contaminants, pesticides and veterinary drugs variables, in spring waters, located in rural properties, which are used for human consumption, in regions of the State of Rio Grande do Sul, under different land uses and occupation, as well as compare with the required potability standards and correlate these variables. The research had as conditions of land use and occupation: native forest (public domain properties), and production areas with swine activities and soy and tobacco crops. Each condition of land use and occupation consisted of five replications and two collections in 2019 (May and November). Statistical analyzes of physical, chemical and microbiological variables were performed using the t test for independent samples, confidence intervals, Pearson's linear correlation through pairs and canonical coefficients and grouping analysis. Due to the microbiological variables and the pH and apparent color, the spring waters studied are not potable, as they are not in compliance with the current Brazilian legislation and the World Health Organization. The analysis of Pearson's correlation between canonical coefficients, showed that the variables total alkalinity, total hardness and electrical conductivity have a positive correlation of wide magnitude, the same occurring between turbidity, apparent color, true color and total iron, between total iron and nitrite and between turbidity and total coliforms. With regard to canonical pairs, a positive correlation of wide magnitude between total iron and nitrate was observed with electrical conductivity and between total ammonia and total alkalinity. Due to the contribution of the total coliforms present in the native forest springs, through the grouping analysis that differed it from the other conditions of land use. Veterinary and pesticide drugs were found in all conditions of land use and occupation under study, which shows that land uses do not interfere in the absence of residues of emerging environmental contaminants. The herbicide Clomazona was found in 95% of water samples and collections. Most rural properties are classified with good preservation. However, the waters of the studied springs are not suitable for human consumption from the perspective of physical, chemical and microbiological variables compared with VMP by legislation.